2019
DOI: 10.1108/mrr-02-2018-0095
|View full text |Cite
|
Sign up to set email alerts
|

Latino entrepreneurs and social media adoption: personal and business social network platforms

Abstract: Purpose The purpose of this paper is to examine both the Latino/Hispanic entrepreneurs’ social media adoption (SMA) for business purposes and the influence of culture on personal versus business social network platform (SNP) selection. Design/methodology/approach The Technology Acceptance Model’s (TAM) factors of perceived usefulness (PU) and perceived ease of use (PEU) as drivers of Latino/Hispanic entrepreneurs’ social network platform selection are examined as well as the effect of SMA on revenue. Data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
2
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 84 publications
(112 reference statements)
0
44
2
15
Order By: Relevance
“…To cope with large-scale corporations, entrepreneurs can exploit the technology of social media as an important instrument to establish customer relationships and a quicker and cheaper communication other than face-to-face communication. Take Facebook, as it delivers a capability to focus on niche markets with lower expenditure than traditional media [4]. Facebook users are increasingly using the site to conduct commercial activities, by posting advertisements in groups and then buying or selling items from each other [5].…”
Section: Introductionmentioning
confidence: 99%
“…To cope with large-scale corporations, entrepreneurs can exploit the technology of social media as an important instrument to establish customer relationships and a quicker and cheaper communication other than face-to-face communication. Take Facebook, as it delivers a capability to focus on niche markets with lower expenditure than traditional media [4]. Facebook users are increasingly using the site to conduct commercial activities, by posting advertisements in groups and then buying or selling items from each other [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous research on social media in SMEs including the effect of social media on performance [5][6][7][8][9][10] social media for SMEs knowledge management [11]; social media for recruitment in SMEs [12]; and social media as tool for facilitating knowledge creation and innovation in SMEs [13]. Some previous studies also looked at factors that influenced social media adoption in SMEs [6,14,15,16,17,10,18]. Most of the research was carried out in developed countries [5,19,20,21,15,16,17,18,22] and only few research has been done in developing countries [6,14,18], where no one has used the UTAUT model approach in predicting the factors of social media adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies also looked at factors that influenced social media adoption in SMEs [6,14,15,16,17,10,18]. Most of the research was carried out in developed countries [5,19,20,21,15,16,17,18,22] and only few research has been done in developing countries [6,14,18], where no one has used the UTAUT model approach in predicting the factors of social media adoption. We see that very little research has focused their studies on SME entrepreneurs' intentions to adopt social media to market their products using UTAUT model as a vacancy or research gap that needs to be investigated further.…”
Section: Introductionmentioning
confidence: 99%
“…Statista reports that in 2017, there were 2.46 billion social media users (Figure 1) [2,3]. Social media can be classified into blogs, social networking sites, virtual social worlds, collaborative projects, communities and virtual gaming worlds [4]. There are indications that explain the role of social media increasingly varied, not only limited to tools for social communication [5], but also began to be used for business purposes.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand why and how social media was adopted for business and for what purpose [11]. Gavino et al see further research on relevant and validated measurements of the impact of social media use on business performance and corporate income [4]. Lockett found that SME businesses generally do not have the tools and strategies for using social media [10].…”
Section: Introductionmentioning
confidence: 99%